Love's first bloom - Parr, Delia (Bethany House, 2010)
Ruth Livingstone's life changes drastically the day her father puts a young child in her arms and sends her to a small village in New Jersey under an assumed name. There Ruth pretends to be a widow and quietly secludes herself until her father is acquitted of a crime. But with the emergence of the penny press, the imagination of the reading public is stirred, and her father's trial stands center stage. Asher Tripp is the brash newspaperman who determines that this case is the event he can use to redeem himself as a journalist. Ruth finds solace tending a garden along the banks of the Toms River--a place where she can find a measure of peace in the midst of the sorrow that continues to build. It is also here that Asher Tripp finds a temporary residence, all in an attempt to discover if the lovely creature known as Widow Malloy is truly Ruth Livingstone, the woman every newspaper has been looking for. Love begins to slowly bloom...but is the affection they share strong enough to withstand the secrets that separate them?